Comparative analysis of heat and water resources and their effects on agriculture layout in the east and west parts of subtropic mountainous areas in China - LI Quansheng (浙江大学学报. 农业与生命科学版)
Based on analysis of fixed position climate observation and on-the-spot investigation in the east and west parts of subtropic mountainous areas in China, the laws of heat and water resources spacetime distribution were studied comparatively, the effects on agriculture layout were discussed.